1984
DOI: 10.1111/j.2044-835x.1984.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of events in space: Young infants are not always egocentric

Abstract: Factors associated with spatial reference in a small-scale space were investigated in three experiments. Subjects were first trained to anticipate an event at one specific location from two different directions of facing. They were then required to locate this event from a novel direction. Both 6-and 8-month infants visually anticipated the whereabouts of the event from the novel direction and displayed persistent visual fixation towards the place where it had previously appeared. For 8-month infants, successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…The 9-and 11-month-olds responded egocentrically in the absence of landmarks but correctly in the presence of landmarks. McKenzie, Day, and Ihsen (1984) reported similar results.…”
Section: Development Of Place Learning and Cue Learning In Infantssupporting
confidence: 63%
See 1 more Smart Citation
“…The 9-and 11-month-olds responded egocentrically in the absence of landmarks but correctly in the presence of landmarks. McKenzie, Day, and Ihsen (1984) reported similar results.…”
Section: Development Of Place Learning and Cue Learning In Infantssupporting
confidence: 63%
“…Although the previously mentioned studies found no evidence of cue use in infants under 9 months of age, a few studies found that infants can be trained to use cues with enough practice trials (e.g., Cornell & Heth, 1979;McKenzie et al, 1984), suggesting that younger infants may be able to use direct landmarks given the right task and training. This raises the issue of why infants in the current experiment seemed to be unable to use the direct landmark, whereas in other studies they could.…”
Section: Discussionmentioning
confidence: 88%
“…Earlier work assigned development of the ability to appreciate another person's point of view (that it was different from one's own and that what might be visible or occluded for that person was not the same as for oneself) to a rather late age, but as better ways of testing the activities and knowledge of younger children were found, the age was progressively lowered. McKenzie et al (1984) found that six-and eight month-old infants could locate an anticipated event from a novel direction after rotation, and did not search always in a constant direction relative to themselves. The rotations were 30 or 60 degrees to the right or left of the child's original position.…”
Section: What Is Around the Cornermentioning
confidence: 95%
“…How does memory for locations change during the preschool years? Early research focused on young children's use of egocentric and allocentric cues (e.g., Acredolo, 1977Acredolo, , 1978McKenzie, Day, & Ihsen, 1984). For example, Acredolo and Evans (1980) showed that egocentric responding declined during the first year of life.…”
Section: Illinois State Universitymentioning
confidence: 99%